INTERSTELLAR EXTINCTION LAW FOR THE PLEIADES - MENDOZA, EUGENIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1965)
We have made (U, B, V, R, I, J, K) photometric observations on a reddened AO V star, which is a member of The Pleiades (Hz 371). These data have been interpreted in terms of the interstellar extinction law. If we determine the ratio of total-to-selective
BOL OBS TONAN TACUB
Keywords: INTERSTELLAR, EXTINCTION, LAW, PLEIADES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS